Analysis of Social Capital in the Women Farmers Group of Dorang Cinta, Surabaya City - Dwiyana Anela Kurniasari; Andri Krisna Dianto (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2021)
Social capital is one of the capitals that can be used for farmers to strengthen their groups. This social capital is one aspect that can make people join so that they can achieve common goals based on the aspect of togetherness, bound by trust, based on norms and values ​​that are upheld and adhered to by the community as well as a good communication network. The aims of this study are: (1) To describe the social and economic conditions of the members of the Dorang Cinta Women's Farmer Group in Surabaya. (2) Analyzing social capital in the Dorang Cinta Women's Farmer Group, Surabaya City. The location of the research was carried out purposively, namely in RT 10 RW 03, Perak Barat Village, Krembangan District, Surabaya City in the Dorang Cinta Women's Farmer Group. The data used in this study are primary data and secondary data. The data analysis method in this study is a descriptive method using a questionnaire containing a list of questions that have been compiled in the form of a Likert scale. Analyzing social capital consists of several elements, namely: (1) Trust and Norms. The conclusion of this study is that the social capital of members of the Dorang Cinta Women's Farmer Group is included in the high category, namely 3.66. The assessment of each element of social capital which consists of trust and norms is included in the high category.